2014
DOI: 10.1007/s12031-014-0284-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Protects the Brain Against Ischemic Reperfusion Injury in a Transient Model of Focal Cerebral Ischemia

Abstract: Hydrogen sulfide (H(2)S), a well-known toxic gas, is regarded as endogenous neuromodulator and plays multiple roles in the central nervous system under physiological and pathological states, especially in secondary neuronal injury. Recent studies have shown relatively high concentrations of hydrogen sulfide (H(2)S) in the brain and also cytoprotective effects of endogenous and exogenous H(2)S in models of in vitro and in vivo ischemic injury. H(2)S protects neurons by functioning as an anti-oxidant, anti-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…Gheibi et al (2014) reported that 1 and 5 mg NaHS (an H 2 S donor) intraperitoneally injected at the beginning of ischemia reduced brain edema in a dose-dependent manner. However, Johansen et al (2006) demonstrated that the concentrationdependent protective action of NaHS was not observed at 10 μM in the perfused heart model.…”
Section: Discussionmentioning
confidence: 99%
“…Gheibi et al (2014) reported that 1 and 5 mg NaHS (an H 2 S donor) intraperitoneally injected at the beginning of ischemia reduced brain edema in a dose-dependent manner. However, Johansen et al (2006) demonstrated that the concentrationdependent protective action of NaHS was not observed at 10 μM in the perfused heart model.…”
Section: Discussionmentioning
confidence: 99%
“…confirmed that the protective effect of NaHS on myocardium against ischemic/ reperfusion injury protection was not concentration-dependent. While the study of Gheibi et al [50]. in which a MCAO model was applied, the authors found that intraperitoneal injection of NaHS alleviated brain edema and the protective effect was dose-dependent.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…DNA fragmentation and apoptotic cell death were detected using a TUNEL assay [26,27]. TUNEL staining was performed using an In Situ Cell Death Detection Kit (Roche, Mannheim, Germany), a kit for the detection and quantification of apoptosis on the single cell level, based on labeling of DNA stand breaks, according to the manufacturer's protocol.…”
Section: Tunel Stainingmentioning
confidence: 99%